The Impact of Adverse Childhood Experiences on Youth’s Mental Health: What is the Role of Family Resilience? - Jusuk Song; Hyuncheol Yoon; Mihee Woo; Isak Kim (Journal of Child & Adolescent Trauma, 2026)
Abstract Given that many adverse childhood experiences (ACEs) are family-contextual and that family processes shape youth mental health, the current study examined the role of family resilience in the relationship between ACEs and major mental health outcomes among youth aged 6–17 years. We employed the data from 2022 National Survey of Children’s Health in the United States. Structural equation modeling was estimated using the mean- and variance-adjusted weighted least squares estimator (WLSMV) given the categorical nature of the data. The study results revealed a good model fit (CFI = 0.974, TLI = 0.969, RMSEA = 0.028, and SRMR = 0.044). Statistically significant pathways were found between ACEs and mental health outcomes ( β = 0.50, p < .001), ACEs and family resilience ( β = − 0.19, p < .001), and family resilience and mental health outcomes ( β = − 0.11, p < .001). Additionally, family resilience showed a significant indirect effect on the relationship between ACEs and mental health outcomes ( β = 0.02, p < .001). These findings highlight the potential role of family-oriented approaches for effective trauma prevention and youth mental health interventions.